Politik Hukum Pengelolaan Wilayah Perbatasan Berbasis Pemenuhan Hak Konstitusional Warga Negara - Yahya Ahamad Zein (Fakultas Hukum Universitas Islam Indonesia, 2016)
The main problem of this research is the legal politics of border area management which is based on the fulfillment of citizens’ constitutional rights. This research was a normative legal research, which is a research which is related to the norms found in the Constitution 1945 as well as other constitutions which are related to the research objects, by using statute approach. The findings show conclude that legal politics of border area management is found in Law Number 3 of 2002 concerning National Defense, Law Number 17 of 2007 concerning National Long-Term Development Plan in 2005 – 2025 and Law Number 43 of 2008 concerning State Territory are generally still oriented on security approach; although they have also employed prosperity approach, they have not maximized the management of border areas. This is because the prosperity approach is not accompanied by the fulfillment of basic social rights which become the constitutional rights of the citizens in border areas